Exploring the roles, challenges, and coping mechanisms of administrative staff in supporting academic staff at higher education institutions / Nur Hafizah Adnan - Adnan, Nur Hafizah (2024)
At higher education institutions, academicians or faculty have always been the focus, shadowing the administrative staff, whose roles are equally important. This is evidenced by limited studies on administrative staff in higher education institutions. Their roles are always hidden behind a desk, their challenges are unheard of, and their coping strategies are less explored. This brings about the need to understand better how administrative staff support academic staff in higher education institutions. Thus, this research explores how they perceived their roles in supporting the academic staff, their challenges and how they cope with the challenges in higher education institutions. This study is specific to one of the private universities in Kuala Lumpur. A descriptive qualitative design was adopted with a semi-structured interview employed to obtain the qualitative data. A total of 12 administrative staff were interviewed and the data was analysed using thematic analysis. A total of eleven themes were established based on the context of exploration. The first three themes emerged from administrative staff’s perception of their roles namely the supportive role of the academic leader, an intermediary role for stakeholders and important pillars to the institutions. The following four themes revolved around the challenges faced by administrative staff which include barriers to communication, academic leadership styles, academic staff attitude and the sense of being undervalued. The last four themes focused on their coping strategies namely managing themselves, obtaining social support and coping spiritually. The study suggested that addressing these implications with a supportive and collaborative environment can contribute to the success of both administrative and academic staff in ensuring the smooth running of the educational institution.